2019
DOI: 10.1105/tpc.19.00169
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-associated chloroplast SRP54 enables efficient co-translational membrane insertion of key photosynthetic proteins

Abstract: Key proteins of the photosynthetic complexes are encoded in the chloroplast genome and cotranslationally inserted into the thylakoid membrane. However, the molecular details of this process are largely unknown. Here, we demonstrate by ribosome profiling that the conserved chloroplast signal recognition particle subunit (cpSRP54) is required for efficient cotranslational targeting of several central photosynthetic proteins, such as the PSII PsbA (D1) subunit, in Arabidopsis (Arabidopsis thaliana). High-resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 68 publications
3
43
0
Order By: Relevance
“…While the post-translational targeting pathway of cpSRP54 and cpSRP43 is relatively well understood, reviewed in [106], rather little is known about the co-translational function and the mechanism of target protein integration into thylakoid membranes. At least in Pisum sativum, binding to the ribosome is proposed to occur via the M domain interacting with the surface-exposed part of uL4c, a ribosomal protein of the large subunit ( Figure 2) [107]. For many years cpSRP54 was only known to co-translationally associate with the photosystem II (PS II) core subunit PsbA and the cytochrome b 6 f complex subunit PetB [108][109][110].…”
Section: Co-translational Targeting Of Chloroplast-encoded Proteins Tmentioning
confidence: 99%
See 4 more Smart Citations
“…While the post-translational targeting pathway of cpSRP54 and cpSRP43 is relatively well understood, reviewed in [106], rather little is known about the co-translational function and the mechanism of target protein integration into thylakoid membranes. At least in Pisum sativum, binding to the ribosome is proposed to occur via the M domain interacting with the surface-exposed part of uL4c, a ribosomal protein of the large subunit ( Figure 2) [107]. For many years cpSRP54 was only known to co-translationally associate with the photosystem II (PS II) core subunit PsbA and the cytochrome b 6 f complex subunit PetB [108][109][110].…”
Section: Co-translational Targeting Of Chloroplast-encoded Proteins Tmentioning
confidence: 99%
“…For many years cpSRP54 was only known to co-translationally associate with the photosystem II (PS II) core subunit PsbA and the cytochrome b 6 f complex subunit PetB [108][109][110]. An elegant recent ribosome profiling study comparing thylakoid association of translating ribosomes in A. thaliana wild-type and srp54 mutant lines greatly extending the pool of putative cpSRP54 substrates [107]. This ribosome profiling approach showed that the loss of cpSRP54 does not generally result in different footprint yields or altered translational output of all plastid open reading frames (ORFs), but there was a clear decrease in membrane protein footprint yield of putative substrate proteins, showing the Plants 2020, 9, 214 7 of 15 importance of cpSRP54 for protein integration into thylakoid membranes.…”
Section: Co-translational Targeting Of Chloroplast-encoded Proteins Tmentioning
confidence: 99%
See 3 more Smart Citations